Representation of Educational Values in Sang Pemimpi’s Novel and Its Relevance for the Development of Literary Learning in Secondary Schools - Berliana Wahyu Ningtyas; Anwar Efendi; Suroso; Ridwan Tawaqal; Safrina Ilmi Nur Azizah (Cita konsultindo, 2026)
The purpose of this study is to explain (1) the educational value contained in the novel Sang Pemimpi by Andrea Hirata and (2) the relevance of the educational value contained in the novel Sang Pemimpi to Indonesian Language education in SMA/MA. This research is a qualitative descriptive study. The primary data source of this research is Sang Pemimpi novel by Andrea Hirata itself. The secondary data sources are obtained from references that are relevant to the research problem. The research data was obtained by using library research techniques and note- taking methods. The data obtained were analyzed using the flow analysis technique. The validity of the data was obtained through triangulation validity and intrarater and interrater reliability. This research will show the following points. First, the educational values contained in Sang Pemimpi novel are divine or religious values, moral values, and social values. The divine or religious values presented are in the form of praying and reciting, applying religious knowledge, being steadfast in living life, heartfelt, being grateful, and believing in destiny. Moral values which include cooperation, discipline, active learning, independence, responsibility, mutual forgiveness, and courage in life. The social values presented by Andrea Hirata in this are the willingness to sacrifice and love. Second, the relevance of the educational value contained in Sang Pemimpi novel to Indonesian language education in SMA/MA is that this novel can be used as teaching material or media for educating literary texts in XII class. The basic competence related to this research is basic competence 3.9 in XII class, it is analyzing the content and language of the novel